(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article shows the concepts of electronic digital signature and the main goals of its use. In addition, the science "Cryptography", which is the basis of electronic signature, and the initial encryption algorithms of this science are presented, showing examples of them. raised Electronic digital signature algorithms based on the complexity of the factorization problem